2005
DOI: 10.1063/1.2036967
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of nanotubes revisited: Effects of chirality, isotope impurity, tube length, and temperature

Abstract: We study the dependence of thermal conductivity of single walled nanotubes (SWNT) on chirality, isotope impurity, tube length and temperature by nonequilibrium molecular dynamics method with accurate potentials. It is found that, contrary to electronic conductivity, the thermal conductivity is insensitive to the chirality. The isotope impurity, however, can reduce the thermal conductivity up to 60% and change the temperature dependence behavior. We also found that the tube length dependence of thermal conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
213
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(234 citation statements)
references
References 38 publications
19
213
0
2
Order By: Relevance
“…Theoretical predictions that the intrinsic thermal conductivity K -limited by the crystal anharmonicy alone -can diverge with the crystal size L in 2D and 1D systems, continue to ignite debates [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Theoretical studies of the lattice thermal transport in 2D anharmonic Fermi-Pasta-Ulam (FPU) lattices [2][3], 2D…”
Section: Context Imagementioning
confidence: 99%
“…Theoretical predictions that the intrinsic thermal conductivity K -limited by the crystal anharmonicy alone -can diverge with the crystal size L in 2D and 1D systems, continue to ignite debates [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Theoretical studies of the lattice thermal transport in 2D anharmonic Fermi-Pasta-Ulam (FPU) lattices [2][3], 2D…”
Section: Context Imagementioning
confidence: 99%
“…The isotope effects on thermal conductivity of carbon nanotubes have been investigated by MD simulations, 45 and it is found that the thermal conductivity of carbon nanotubes can be reduced more than 50% with isotope impurity. Later, this large reduction by isotopic doping effect has been confirmed experimentally.…”
Section: A 1d Nanostructuresmentioning
confidence: 99%
“…63 Zhang and Li calculated the temperature dependence of thermal conductivity of (5,5) single-wall carbon nanotubes (SWCNTs). 45 Fig. 1 shows the length dependent thermal conductivity of SWCNT at 300 K and 800 K, respectively.…”
Section: A 1d Nanostructuresmentioning
confidence: 99%
“…One new work [32] showed that a finite thermal conductivity can be reached only when disorder exists in the 1D chain. Furthermore, Zhang and Li [33] reported the value of the exponent for (5, 5) and (10, 10) single-wall CNTs (SWCNTs) at 300 K and 800 K. Their results showed that at 300 K the (5, 5) SWCNT follows the law of 2/5 and the exponent of (10, 10) SWCNT is 0.36. Recently, the thermal conductivity of (10,0) SWCNTs was suggested to be proportional to L 1/2 [34].…”
Section: Thermal Conductivity and Specific Heat Of Swsntsmentioning
confidence: 99%